Health Related Quality of Life in Iranian Elderly Citizens: A Systematic Review and Meta-Analysis - Mohammad Farajzadeh; Reza Ghanei Gheshlagh; Kourosh Sayehmiri (Shiraz University of Medical Sciences, 2017)
Background: The ever-growing elderly population of Iran and their physical and mental consequences put emphasis on the necessity of determining the quality of life (QoL) in this social group. This systematic review and meta-analysis aimed to estimate the mean score of QoL in Iranian elderly citizens. Methods: Twenty-one articles that were indexed in Iranian (MagIran and Iran Medex) and international (Scientific Information Database, Google Scholars, Science Direct, PubMed, ProQuest, Scopus) databases were selected. The articles have used the Short Form Health Survey (SF-36) to measure QoL in Iranian elderly. The collected data were analyzed using a random effects model, while heterogeneity of the studies was measured by I2 index. The data analysis was performed by STATA. Results: The sample size of the 21 articles was 5318 and the mean score of QoL in the healthy and sick elderly citizens was 53.8 (CI 95%: 49.4-58.2) and 50.6 (CI 95%: 38.4-62.9) respectively. In addition, there was no significant relationship between the score of QoL and the year of publication of the articles. (P=0.748) Conclusion: Given that QoL of the studied elderly was almost at an average level, there is a need to codify and implement comprehensive programs through effective training programs toward improving QoL of the elderly.